2014
DOI: 10.1248/cpb.c14-00169
|View full text |Cite
|
Sign up to set email alerts
|

<i>cis</i>-Cinnamic Acid Selective Suppressors Distinct from Auxin Inhibitors

Abstract: The activity of cis-cinnamic acid (cis-CA), one of the allelochemicals, in plants is very similar to that of indole-3-acetic acid (IAA), a natural auxin, and thus cis-CA has long been believed to be an analog of auxin. We have reported some structure-activity relationships studies by synthesizing over 250 cis-CA derivatives and estimating their inhibitory activities on root growth inhibition in lettuce. In this study, the compounds that showed low-or no-activity on root growth inhibition were recruited as cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Therefore, we endeavored to discover inhibitors of gravitropic bending that did not suppress primary root elongation among our synthetic analogues of cis-CA. After screening the synthetic cis-CA analogues, especially the less potent elongation inhibitory compounds (Okuda et al, 2014), we found that (2Z,4E)-5-phenylpenta-2,4-dienoic acid (ku-76, Figure 2) inhibited root gravitropism at 5 M, but did not repress primary root elongation at the 5-50 M (Fujii et al, 2016). As such, ku-76 was considered to specifically target regulatory component of root gravitropic bending.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we endeavored to discover inhibitors of gravitropic bending that did not suppress primary root elongation among our synthetic analogues of cis-CA. After screening the synthetic cis-CA analogues, especially the less potent elongation inhibitory compounds (Okuda et al, 2014), we found that (2Z,4E)-5-phenylpenta-2,4-dienoic acid (ku-76, Figure 2) inhibited root gravitropism at 5 M, but did not repress primary root elongation at the 5-50 M (Fujii et al, 2016). As such, ku-76 was considered to specifically target regulatory component of root gravitropic bending.…”
Section: Introductionmentioning
confidence: 99%
“…cis-CA has also been reported to have inhibitory activity of auxin efflux 18 . We previously reported that cis-CA is localized at the root tip of lettuce by molecular imaging experiments using fluorescent molecular probes of cis-CA [21][22][23][24] . Based on these results, we subsequently focused on the effect of cis-CA on the gravitropism of plants and observed that it inhibits not only lettuce root elongation but also gravitropic bending of the roots, that is, cis-CA is a non-selective inhibitor of both elongation and gravitropic bending.…”
mentioning
confidence: 99%